The auroral break-up as related to the interplanetary parameters and the geomagnetic activity - Silbergleit, V. M. (1994)
In the present study, we used as a significant indicator of the auroral break-up the "sudden equatorward shift" in arcs or displays. For the dark months of May and June of 1971, auroral observations at Base General Belgrano (78,0° S; 38,8° W) were used. Four-hourly sequences centered at the break-up (t=0) were studied for the following quantities: a) The magnitude of the interplanetary magnetic field (B), b) The southward component of the interplanetary magnetic field (Bz), c) The solar wind speed (V), d) The solar wind electric field (the westward component: E ), e) The auroral electrojet magnetic activity indices (AE, AL, AU). On the basis of the seven substorms studied, one may deduce that an appreciable increase of geomagnetic activity occured about 40 minutes after the energy arrival at the magnetosphere, but it is not enough strong to take place the break-up, it will happen after another period of 35 minutes. This result confirms that a substorm only occurs after a build-up process. The present paper also confirms the possibility of using the auroral zone geomagnetic activity for estimating the solar wind velocity.